BASIC STRATEGIC TOOLS FOR ANALYZING THE COMPANY’S FINANCIAL AND PRODUCTION POTENTIAL: THE CASE OF “TROPIK” LLC - Kulinich , Tetiana; Bing , Wang (Collection of scientific papers «ΛΌГOΣ», 2024)
The article discusses the strategic toolkit for analyzing the company’s financial and production potential. The main tool of the strategic toolkit in this case is the SWOT analysis, the partial basis for which is the ratio analysis. This toolkit was used to make strategic decisions regarding the future development of “Tropik” LLC. When evaluating the financial and production potential of this company, a limited list of indicators was used, focused on the assessment of individual components of assets and capital, revenue, expenses, and profit. As a result, the main attention is paid to the characteristics of the consequences of business activity management, the use of fixed assets, the solvency ensuring, the formation of the capital structure, and obtaining a certain level of coefficients of profitability of sales, assets, and equity. The indicated technique was used in the example of “Tropik” LLC, for which strategic steps were proposed taking into account the existing potential.